A small-diameter vascular graft immobilized peptides for capturing endothelial colony-forming cells - Yaqi Tang; Lu Yin; Shuai Gao; Xiaojing Long; Zhanhui Du; Yingchao Zhou; Shuiyan Zhao; Yue Cao; Silin Pan (Frontiers in Bioengineering and Biotechnology, 2023)
Combining synthetic polymers and biomacromolecules prevents the occurrence of thrombogenicity and intimal hyperplasia in small-diameter vascular grafts (SDVGs). In the present study, an electrospinning poly (L)-lactic acid (PLLA) bilayered scaffold is developed to prevent thrombosis after implantation by promoting the capture and differentiation of endothelial colony-forming cells (ECFCs). The scaffold consists of an outer PLLA scaffold and an inner porous PLLA biomimetic membrane combined with heparin (Hep), peptide Gly-Gly-Gly-Arg-Glu-Asp-Val (GGG-REDV), and vascular endothelial growth factor (VEGF). Attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS), and contact angle goniometry were performed to determine successful synthesis. The tensile strength of the outer layer was obtained using the recorded stress/strain curves, and hemocompatibility was evaluated using the blood clotting test. The proliferation, function, and differentiation properties of ECFCs were measured on various surfaces. Scanning electronic microscopy (SEM) was used to observe the morphology of ECFCs on the surface. The outer layer of scaffolds exhibited a similar strain and stress performance as the human saphenous vein via the tensile experiment. The contact angle decreased continuously until it reached 56° after REDV/VEGF modification, and SEM images of platelet adhesion showed a better hemocompatibility surface after modification. The ECFCs were captured using the REDV + VEGF + surface successfully under flow conditions. The expression of mature ECs was constantly increased with the culture of ECFCs on REDV + VEGF + surfaces. SEM images showed that the ECFCs captured by the REDV + VEGF + surface formed capillary-like structures after 4 weeks of culture. The SDVGs modified by REDV combined with VEGF promoted ECFC capture and rapid differentiation into ECs, forming capillary-like structures in vitro. The bilayered SDVGs could be used as vascular devices that achieved a high patency rate and rapid re-endothelialization.